2018
DOI: 10.1002/slct.201800227
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Zwitterionic Molten Salt: An Efficient Organocatalyst under Neat Conditions at Room Temperature for the Synthesis of Dipyrromethanes as well as Bis(indolyl)methanes

Abstract: An imidazole-based zwitterionic-salt, 4-(3-methylimidazolium) butane sulfonate (MBS), has been found to be an efficient organocatalyst for the synthesis of dipyrromethanes as well as bis(indolyl)methanes at room temperature under solvent-free conditions (neat) in high yields. The reaction procedure is very simple and a large variety of aldehydes have been examined under similar conditions for indoles and pyrroles. The catalytic reaction proceeded very smoothly and showed high chemoselectivity. Clean reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…The selectivity toward dipyrromethane was always maintained at approximately 90%. Such high yield and selectivity were comparable to those of reported homogeneous and heterogeneous catalytic systems [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 11 , 13 ]. Impressively, even after the running time was prolonged to more than 12 h, the conversion and yield did not show a significant decrease.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The selectivity toward dipyrromethane was always maintained at approximately 90%. Such high yield and selectivity were comparable to those of reported homogeneous and heterogeneous catalytic systems [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 11 , 13 ]. Impressively, even after the running time was prolonged to more than 12 h, the conversion and yield did not show a significant decrease.…”
Section: Resultssupporting
confidence: 87%
“…Some reports have proved that this type of catalyst has high catalytic activity in dipyrromethane synthesis. For instance, imidazole-based zwitterionic salts under solvent-free conditions and SO 3 H-IL ([bsmim][HSO 4 ]) in the aqueous phase were adopted as homogeneous catalysts in this process by Chatterjee et al and Senapak et al [ 11 , 13 ], respectively, and both showed excellent catalytic activity. Although these ionic liquids have been proven with high catalytic activity, the requirement of a long reaction time and difficulty in the recovery and reuse of ionic liquids after reaction for dipyrromethane synthesis are still challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The research group of Majee explored the use of imidazolium zwitterionic molten salt as organocatalyst in the synthesis of meso -substituted dipyrromethanes under solvent-free conditions (Scheme 25) [84]. This catalytic system acts as an electrophilic activator of the aldehyde by the hydrogen bond with imidazolium C-2 hydrogen, emphasizing the importance of this cationic moiety.…”
Section: Novel Synthetic Strategiesmentioning
confidence: 99%
“…Dipyrromethanes with a naphthyl 108b , pyrrole or indole 108c , and propyl 108d substituents were also synthesized in high yields, using the same imidazolium zwitterionic molten salt as catalyst. The methodology developed was seen by the authors as being a green synthetic protocol, because it was metal- and solvent-free, and environmentally friendly with a good atom economy [84].…”
Section: Novel Synthetic Strategiesmentioning
confidence: 99%
“…A few protocols are reported in literature using various catalyst and solvent such as enzymes, [21] meglumine, [22] thiamine hydrochloride, [23] graphene oxide, [24] ethyl lactate, [25] sulphated polyborate, [26] Lewis acids, [27–32] Brønsted acids, [33] heteropoly acids, [34–36] solid acids, [37–42] ionic liquids, [43] metal complexes, [44–46] 4‐sulfophthalic acid [47] and Iodine/tert‐Butyl Hydroperoxide [48] . Recently, a number of methodologies have been developed in this field [49–68] . A generalize scheme for the different processes so far reported in literature are drawn in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%